2010
DOI: 10.17221/200/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of solid-liquid extraction process of total polyphenols from soybeans

Abstract: Jokić S., Velić D., Bilić M., Bucić-Kojić A., Planinić M., Tomas S. (2010): Modelling of the process of solid-liquid extraction of total polyphenols from soybeans. Czech J. Food Sci., 28: 206-212.The influence of the solvent, temperature, and extraction time on the extractability of total polyphenols from milled soybeans variety Ika was investigated. The study was performed in order to select the most suitable solvent (water; 50, 60, 70, and 80% aqueous ethanol) for achieving the highest yield of total polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 18 publications
10
80
0
7
Order By: Relevance
“…The same trend was observed on the bottom phase. The increase of temperature resulted in most cases in an increase of diffusion rate and solubility of the extracted substances (Jokic et al 2010). On the other hand, temperature had no influence on the recovery yield (Y), which hardly varied with temperature.…”
Section: Effect Of Temperaturementioning
confidence: 97%
“…The same trend was observed on the bottom phase. The increase of temperature resulted in most cases in an increase of diffusion rate and solubility of the extracted substances (Jokic et al 2010). On the other hand, temperature had no influence on the recovery yield (Y), which hardly varied with temperature.…”
Section: Effect Of Temperaturementioning
confidence: 97%
“…Better quantities of phenolics were obtained using a 50:50% ethanol-water ratioand an ET of 30 min. Jokić et al (2010) evaluated the influence of water and ethanol at different concentrations (50, 60, 70, 80%), temperatures (25, 40, 50, 60, 70, 80 °C), and extraction times (5, 10, 15, 20, 30, 40, 60, 90, 120 min) on the extraction of total phenols of soybeans, Ika variety, using an average particle size of 0.459 mm and a liquid-solid ratio of 20 mL/g. The total phenols concentration increased as temperature increased.…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 99%
“…Another important factor is the temperature of extraction. It has been found that increasing the temperature for extraction, up to 80 °C, increases the yields of total phenols in soy extracts using soy powder with an average particle size of 0.459 mm (Jokić et al, 2010). However, the use of temperatures higher than 70 °C for prolonged periods may cause significant degradation of anthocyanins (Cissé, Vaillant, Acosta, Dhuique-Mayer, & Dornier, 2009;Gartaula & Karki, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic modelling is of great importance for understanding complex diffusion, mass transfer, and thermodynamic parameters affecting extraction (Jurinjak Tušek et al, 2016). The most commonly used empirical model is the Peleg's model for the description of moisture sorption curves (Peleg, 1988), adapted for extraction processes (Bucić-Kojić et al, 2007;Jokić et al, 2010;Piwowarska and González-Alvarez, 2012). Other frequently used models for solid-liquid extraction processes are the modified Page's model (Jokić et al, 2010), the logarithmic model, also known as Elovich's model (Kitanović et al, 2008;Jokić et al, 2010), or the parabolic diffusion model (Kitanović et al, 2008;Piwowarska and González-Alvarez, 2012).…”
mentioning
confidence: 99%